The need for speed in advanced non‐small cell lung cancer: A population kinetics assessment. (11th November 2021) - Stewart, David J.; Maziak, Donna E.; Moore, Sara M.; Brule, Stephanie Y.; Gomes, Marcio; Sekhon, Harman; Dennie, Carole; Lo, Bryan; Fung‐Kee‐Fung, Michael; Bradford, John‐Peter; Reaume, Martin Neil
Abstract: Background: Systemic therapy prolongs overall survival (OS) in advanced non‐small cell lung cancer (NSCLC), but diagnostic tests, staging and molecular profiling take time, and this can delay therapy initiation. OS approximates first‐order kinetics. Methods: We used OS of chemo‐naive NSCLC patients on a placebo/best supportive care trial arm to estimate % of patients dying while awaiting therapy. We digitized survival curves from eight studies, calculated OS half‐life, then estimated the proportion surviving after different times of interest ( t n ) using the formula: X = exp ‐ t n ∗ 0 .693 / t 1 / 2, where EXP signifies exponential, * indicates multiplication, 0.693 is the natural log of 2, and t 1/2 is the survival half‐life in weeks. Results: Across trials, the OS half‐life for placebo/best supportive care in previously untreated NSCLC was 19.5 weeks. Hence, based on calculations using the formula above, if therapy were delayed by 1, 2, 3, or 4 weeks then 4%, 7%, 10%, and 13% of all patients, respectively, would die while awaiting treatment. Others would become too sick to consider therapy even if still alive. Conclusions: This quantifies why rapid baseline testing and prompt therapy initiation are important in advanced NSCLC. It also illustrates why screening procedures for clinical trial inclusion must be faster. Otherwise, it is potentially hazardous for a patient to be considered for a trial due to risk of death or deterioration while awaiting eligibility assessment. It is also important to not delay initiation of systemic therapy for procedures that add relatively little value, such as radiotherapy for small, asymptomatic brain metastases. Abstract : In patients with metastatic non‐small cell lung cancer, it takes time for diagnostic and staging tests and for initiation of therapy. Based on exponential decay nonlinear regression analysis of overall survival curves from placebo or best supportive care arms of first line studies in metastatic disease, we calculated that an average of 4% of remaining patients will die during each week that passes without initiation of systemic therapy. It is important to initiate therapy as rapidly as possible.